Scientific evidence on the presence of mental disorders resulting from SARS-CoV-2 infection in people with COVID-19: scoping review (Research, Society and Development, 2022)
Aim: To identify scientific evidence on the presence of mental disorders due to SARS-CoV-2 infection in people diagnosed with COVID-19; identify the types of mental disorders; to describe the pathophysiological association of SARS-CoV-2 infection with mental disorders; and describe the age and sex characteristics. This is a Scoping Review carried out in the following databases: MEDLINE via PubMed, CINAHL, Web of Science, BVS, Cochrane Library, SCOPUS, Embase, LILACS. And on the following sites: Google Scholar, ProQuest Dissertations and Theses and Gray Literature. The descriptors (comorbidity OR sequel OR complications) AND (Mental Health OR Mental disorders OR Mental Illness) AND (SARS-CoV-2 OR COVID-19 OR coronavirus) were used. The inclusion criteria were: articles that answered the guiding question, available in full, with different methodological approaches, online, in English, Spanish and Portuguese. The following were excluded: articles without free access; opinionated letters to the editor; editorials; and books. Ten studies were selected, which pointed to the high prevalence of occurrence of mental disorders in patients diagnosed with COVID-19, its etiology is multifactorial, being attributed to the damage of the infectious process and to the stressors, resulting from the pandemic. The disorders found were: stress disorders; of humor; psychotics; obsessive-compulsive; of anxiety and sleep-wakefulness. Those with the highest prevalence of involvement were anxiety and depression. There was no significant difference in terms of prevalence by sex. The mean age of participants was 46.1 years. Thus, it is necessary to know the possible sequelae of COVID-19, in order to provide comprehensive support to this population.